Sustainable development in Omsk: Lessons for Central Europe - Judith Marquand; Sergey Kostarev (Economic and Environmental Studies (E&ES), 2013)
In the paper, two short development projects in Omsk carried out in 2002-3 and 2005 are discussed. The authors provide some background about Omsk, the projects and the project partners, describe what was done in the projects themselves, outline the results of the projects, draw lessons from the experience gained during the project, paying attention to transferability, and make some recommendations about conducting the planning of sustainable development.
Keywords: 330; sustainable development; Omsk; Central Europe; Small Environmental Projects Scheme; capacity building